Antecedents and consequences of healthiness in café service: Moderating effect of health concern - Song, Myungkeun; Lee, Won Seok; Moon, Joonho (Frontiers in Sustainable Food Systems, 2022)
This study aims to explore the antecedents of consequences of healthiness in café business context. Plus, this study attests the moderating effect of health concern between healthiness and attitude. To attain more vivid response, this research selected Starbucks coffee case. Hygiene, healthiness, nutrition disclosure are the determinants of healthiness. The consequences of healthiness are attitude and purchase intention. Health concern is the moderating variable between healthiness and attitude. Survey is the main instrument, and Amazon Mechanical Turk is used for data collection. The valid observation for data analysis is 455. For hypotheses testing, structural equation model was implemented. Regarding the results, health concern is positively influenced by hygiene and organic, but healthiness is negatively affected by nutrition disclosure. Moreover, it is found that health concern significantly moderates the relationship between healthiness and attitude, and attitudes exerts positive effect on purchase intention.